2022
DOI: 10.1002/cre2.683
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tobacco and nicotine in causing staining of dental hard tissues and dental materials: A systematic review and meta‐analysis

Abstract: Introduction: Dental staining is a common concern for tobacco users. However, little is known about which components of tobacco are responsible for the staining and whether nicotine may be implicated. This is of increasing relevance with the popularity of novel products such as heated-tobacco products and electronic cigarettes (E-cigarettes).Objectives: This systematic review aimed to establish the evidence base for the effect if any, of the various tobacco and nicotine products in causing staining of dental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…It is consistent with the general perception of tobacco smoking as being unhealthy: tar and other combustion products from conventional cigarettes deposit on dental restorations, causing them to become discolored 19 . In contrast, electronic cigarettes, which heat a nicotine-containing liquid to produce an aerosol, produce fewer combustion-related substances, resulting in less severe staining effects 14 , 20 . Dental professionals should educate patients about these differences and emphasize the importance of smoking cessation or switching to less harmful alternatives, especially in cases where the appearance of restorations is a concern.…”
Section: The Aesthetic Impact Of Smoking On Resin-based Dental Restor...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is consistent with the general perception of tobacco smoking as being unhealthy: tar and other combustion products from conventional cigarettes deposit on dental restorations, causing them to become discolored 19 . In contrast, electronic cigarettes, which heat a nicotine-containing liquid to produce an aerosol, produce fewer combustion-related substances, resulting in less severe staining effects 14 , 20 . Dental professionals should educate patients about these differences and emphasize the importance of smoking cessation or switching to less harmful alternatives, especially in cases where the appearance of restorations is a concern.…”
Section: The Aesthetic Impact Of Smoking On Resin-based Dental Restor...mentioning
confidence: 99%
“…After applying the criteria, five studies were chosen for inclusion in the review. (Figure 1, Tables 1-3) [14][15][16][17][18] .…”
Section: Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The first systematic review identified a total of 27 articles that met its inclusion criteria and concluded that "tobacco smoke causes dental staining. There was limited evidence that e-cigarettes and HTPs did cause dental staining that was less intense than that caused by traditional tobacco products" [172].…”
Section: Oral/dental Healthmentioning
confidence: 99%
“…After screening 273 studies, 13 studies were selected for data extraction of which all analysed CS, four analysed ENDS and two analysed THS. Whilst this systematic review only included in vitro studies, the majority of studies in the wider literature relating to smoking and staining of dental materials appear to be in vitro 6 .…”
Section: Commentarymentioning
confidence: 99%